Harlequin Syndrome After Thoracic Paravertebral Block. Issue 3 (1st February 2016) - Nagasaka, Yasuko; Wasner, Gunnar; Sharma, Balram; Fleischmann, Katharine
Abstract : Harlequin syndrome is characterized by the sudden onset of unilateral facial flushing and sweating, often preceded by exercise, excessive heat, or, rarely, regional anesthesia. Although the exact mechanism remains unclear, it is often referred to as transient or permanent interruption of the sympathetic nervous system. We present a case of Harlequin syndrome without Horner syndrome in a patient with unilateral right-sided facial flushing that started shortly after a left-sided thoracic paravertebral nerve block for a mastectomy. We discuss the interruption of the sympathetic and parasympathetic nervous system and the levels of spinal nerve block associated with a thoracic paravertebral nerve block.